Characterization of Brazil mine tailings dams (Research, Society and Development, 2020)
The beneficiation methods used by Brazilian mining companies make the country have a significant number of dams. In this context, this work aimed to characterize these structures according to height, volume, risk category and environmental damage. For this study, we used a quantitative approach and document analysis, which consisted of examining the dam inventory for the year 2019, provided by the National Mining Agency. The results obtained indicate that in Brazil there are 769 registered dams, most of which are in the states of Minas Gerais (45.6%) and Pará (13.5%). It was noted about volume and height that small dams are the majority, corresponding, respectively, to 74.2% and 64.5% of the registered structures. In addition, it was observed that most of the tailings deposited in the dams come from clay and / or sand mining. It was noted that 53.4% of the dams were built in a single stage, however, it is noteworthy that 81 dams have no indication of the construction method employed. Regarding the risk category and associated potential damage, 217 dams are included in class “B” and 44.7% do not have this information. Miners are often required to monitor these structures along with technical inspections to reduce the risk of rupture and increase dam safety.